Caesarean Scar Pregnancy: Surgical Obstacles - Kerisnan, Rathimalar; Vickneswaren Thever Ramasamy (Malaysian Journal of Science Health & Technology, 2022)
As a rare phenomenon, caesarean scar pregnancy has been found to be managed in many ways in literature. However, to date there lacks a general consensus on the management of caesarean scar pregnancy. In modern obstetrics nowadays, the incidence of caesarean deliveries has been rising. Due to the increase in caesarean section rates, the incidence of caesarean scar pregnancies is also on the rise. Even though the optimal management of caesarean scar pregnancy is unclear, the basic management is tailored according to the clinical presentation and fertility concerns of the individual. Herein, we report a case of a ruptured caesarean scar pregnancy which was managed surgically via emergency laparotomy and hysterectomy.